A report on epidemiological study on pesticide poisioning cases in Chitwan - Gyenwali, Deepak
Summary: Hundreds of chemical compounds are used to manage agricultural pests/domestic pests and to control the vectors of public health importance. Despite the associated benefits of pesticide use, there have been concerns on adverse effects of these chemicals in human health. Pesticide exposure has significant negative impacts on human health including acute severe poisoning leading to death and many chronic health effects. The cases of acute poisoning, including suicide attempts, mass poisoning from contaminated food, chemical accidents in industry, unintentional accidents and occupational exposure in agriculture, constitute the most serious health hazard associated with pesticides use. Acute pesticide poisoning is a major cause of emergency department visit in hospitals. However, there lacks enough information of pesticide poisoning in Nepal. The overall objective of the study was to evaluate the epidemiological characteristicts of the pesticide poisoning cases in hospitals in Chitwan district. A hospital based, quantitative , descriptive study was carried out in four major hospitals of Chitwan district vz. Bharatpur Hospital, CMC teaching Hospital, CMS teaching hospital and Ratna Nagar hospital. Perticide exposure record (PER) form which was used for the data collection.